Role of Social Media in Promoting Organic Products in Karnali Province, Nepal - Rokaya, Ammar Bahadur; Pandey, Akhilesh Chandra (KMC Journal, 2024)
This study examines the Karnali Province of Nepal’s use of social media to promote organic products. This research examines the unique influence on the growth and awareness of organic products of the global revolution in communication and marketing tactics sparked by the rapid expansion and widespread adoption of social media platforms. The study digs into the tactics adopted in advertising organic products within the unique context of Karnali Province. Data for the study was collected through a survey questionnaire distributed to 300 respondents. The sampling method utilized a convenience sampling to gather diverse information about social media engagement, the choice of social media platforms, marketing strategies employed on these platforms, awareness levels of organic products, consumer behavior, and the effectiveness of organic product promotion. The survey targeted a representative sample of the population in Karnali province. Using the Smart PLS-4 programme, the study analyzed the data it had obtained, concentrating on testing hypotheses and looking at the correlations between the variables. The outcomes contribute to a wider understanding of using social media to promote organic products in addition to providing knowledge particular to a given location. This study adds to our knowledge of how social media, particularly in remote and rural areas like Nepal’s Karnali Province, may be a potent and successful instrument for promoting organic products. The results offer useful recommendations for digital marketing tactics customized for certain regional contexts and sustainable agriculture to marketers and policymakers.